Precision mass measurements at TITAN with radioactive ions - Kwiatkowski, Anna; Macdonald, T. D.; Andreoiu, C.; Bale, J. C.; Brunner, T.; Chaudhuri, A.; Chowdhury, U.; Ettenauer, S.; Gallant, A. T.; Grossheim, A.; Lennarz, A.; Mané, E.; et al. (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 2013)
Measurements of the atomic mass further our understanding in many disciplines from metrology to physics beyond the standard model. The accuracy and precision of Penning trap mass spectrometry have been well demonstrated at TITAN, including measurements of neutron-rich calcium and potassium isotopes to investigate three-body forces in nuclear structure and within the island of inversion to study the mechanism of shell quenching and deformation. By charge breeding ions, TITAN has enhanced the precision of the measurement technique. The precision achieved in the measurement of the superallowed β-emitter 74Rb in the 8+charge state rivaled earlier measurements with singly charged ions in a fraction of the time. By breeding 78Rb to the same charge state, the ground state could be easily distinguished from the isomer. Further developments led to threshold charge breeding, which permitted capturing and measuring isobarically and elementally pure ion samples in the Penning trap. This was demonstrated via the Q-value determination of 71Ge. An overview of the TITAN facility and recent results are presented herein.